Strategi Pemasaran Industri Konveksi Menggunakan Analisis “SWOT” - Ikhwan Yunus (Ecobuss, 2021)
The development of the convection industry in Indonesia is growing rapidly. This is because the convection industry is an industry that is needed by the community in meeting clothing needs. In addition, clothing itself is experiencing changes in trends and functions, namely being used as an identity attribute, so that the convection business is in great demand in Indonesia. This study uses a qualitative descriptive method with a SWOT analysis to take advantage of opportunities by maximizing strengths, reducing weaknesses and avoiding threats. The strength of the convection business is classified as a promising business. Weaknesses are lack of capital to develop a business, less competent employees are employed. The target market opportunities are very wide. The threat of the existence of illegal imported products on the domestic market either directly or indirectly.